2018
DOI: 10.3389/fimmu.2018.00305
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Invariant Natural Killer T Cells on Humoral Immunity to T-Dependent and -Independent Antigens

Abstract: Vaccination with CD1d-binding glycolipid adjuvants and co-administered protein, lipid, and carbohydrate antigens leads to invariant natural killer T (NKT) cell-dependent enhancement of protective B cell responses. NKT cell activation boosts the establishment of protein antigen-specific B cell memory and long-lived plasma cell (LLPC) compartments. NKT cells may exert a similar effect on some carbohydrate-specific B cells, but not lipid-specific B cells. The mechanisms of action of NKT cells on B cell responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…However, unlike Tfh-derived B cell responses, those driven by NKTfh cells have no potential to generate long-lived plasma cells and memory B cells ( 196 ). NKTfh cells also possess the ability to boost memory B cell responses to T-dependent antigens but not T-independent lipid antigens ( 198 ). In addition, the NKTfh cells can induce limited GC B cell responses in the absence of CD4 + cell help ( 199 ).…”
Section: Other Follicular T Cellsmentioning
confidence: 99%
“…However, unlike Tfh-derived B cell responses, those driven by NKTfh cells have no potential to generate long-lived plasma cells and memory B cells ( 196 ). NKTfh cells also possess the ability to boost memory B cell responses to T-dependent antigens but not T-independent lipid antigens ( 198 ). In addition, the NKTfh cells can induce limited GC B cell responses in the absence of CD4 + cell help ( 199 ).…”
Section: Other Follicular T Cellsmentioning
confidence: 99%
“…[85,86] Natural killer T (NKT) cells, which share characteristics of natural killer (NK) cells and T cells, represent an effective cell subpopulation in pathogen and tumor cell defense. [87,88] The high number and functionality of NKT cells in blood or tumor was demonstrated to directly correlate with better survival in different human cancers. [88] The advantage of NKT cells over conventional T cells may be their pronounced intrinsic anti-tumor activity through their endogenous TCR [88,89] and is triggered by glycolipids presented via CD1d on antigen-presenting cells.…”
Section: Effec Tiveanti G Entarg E Tingmentioning
confidence: 99%
“…Glycolipid-mediated i NKT cell activation also augments antibody production by B cells ( 58 , 59 ). Intranasal administration of α-GalCer and influenza hemagglutinin (HA) vaccine or formalin-inactivated whole-virion vaccine induced higher titers of mucosal IgA and systemic IgG compared to influenza vaccine alone ( 60 62 ).…”
Section: Glycolipid-activated I Nkt Cells Exhibit mentioning
confidence: 99%
“…Although it is well known that follicular helper T (T FH ) cells play a critical role in the stimulation of germinal center B cells for high-affinity antibody production, as well as differentiation of memory B cells and long-lived plasma cells, recent studies have demonstrated that follicular helper NKT (NKT FH ) cells contribute to augmented IgG antibody production by vaccines containing an i NKT cell glycolipid antigen ( 59 , 64 67 ). Immunization of mice with liposomes containing pneumococcal capsular polysaccharide (CPS) and PBS57, an α-GalCer analog, or CPS-α-GalCer conjugate vaccine induced NKT FH cells expressing PD-1 and CXCR5 or PD-1 and ICOS ( 66 , 67 ).…”
Section: Glycolipid-activated I Nkt Cells Exhibit mentioning
confidence: 99%